Charge density wave induced nodal lines in LaTe3 - Shuvam Sarkar; Joydipto Bhattacharya; Pampa Sadhukhan; Davide Curcio; Rajeev Dutt; Vipin Kumar Singh; Marco Bianchi; Arnab Pariari; Shubhankar Roy; Prabhat Mandal; Tanmoy Das; Philip Hofmann; et al. (Nature Communications, 2023)
Abstract LaTe3 is a non-centrosymmetric material with time reversal symmetry, where the charge density wave is hosted by the Te bilayers. Here, we show that LaTe3 hosts a Kramers nodal line—a twofold degenerate nodal line connecting time reversal-invariant momenta. We use angle-resolved photoemission spectroscopy, density functional theory with an experimentally reported modulated structure, effective band structures calculated by band unfolding, and symmetry arguments to reveal the Kramers nodal line. Furthermore, calculations confirm that the nodal line imposes gapless crossings between the bilayer-split charge density wave-induced shadow bands and the main bands. In excellent agreement with the calculations, spectroscopic data confirm the presence of the Kramers nodal line and show that the crossings traverse the Fermi level. Furthermore, spinless nodal lines—completely gapped out by spin-orbit coupling—are formed by the linear crossings of the shadow and main bands with a high Fermi velocity.